Clinical Evaluation Of Direct Composite Resin And Indirect Micro Ceramic Composite Resin Restorations In Class-I Cavity Of Permanent Posterior Teeth - Shikder, AHM Zakir Hossain; Shomi, Kamrun Naher; Saki, Nushrat; Begum, Ferdousi; Mahmud, Kazi Hossain; Alam, Md Shamsul (International Journal of Human and Health Sciences (IJHHS), 2019)
Background:Previous studies have indicated that the clinical performance of direct composite restoration mainly depends on the polymerization shrinkage. The use of micro ceramic inlay technique has proved to be elegant approach to overcome the polymerization shrinkage and improve the marginal adaptation, reduce wear and leakage of posterior restorations. Objectives:To compare the clinical performance between direct composite restorations and indirect micro ceramic composite restorations in occlusal surface of permanent posterior teethof class-I cavity. Results: The result of this study showed that there was no statisticallysignificant difference between two groups in the treatment of occlusal surface ofclass-I cavity of permanent posterior teeth (p > 0.05). It was concluded that indirect micro ceramic composite resin shows no better clinical efficacy than that of direct composite resin in occlusal surface of class-I cavity of permanent posterior teeth International Journal of Human and Health Sciences Vol. 03 No. 02 April’19. Page: 109-115